A scanner darkly [videorecording (DVD)] - Linklater, Richard, 1960-; Linklater, Richard, 1960-; Reeves, Keanu; Downey, Robert, Jr., 1965-; Harrelson, Woody; Cochrane, Rory; Ryder, Winona, 1971-; Dick, Philip K. (Warner Home Video, 2006)
Set in a future world where America has lost the war on drugs, an L.A. undercover agents change their faces along with their identities. One officer's liberal ingestion of the drug "Substance D" causes him to develop a split personality, a notorious drug dealer. Along with his superior officers, the police set up an elaborate scheme to catch his drug dealer alter-ego and tear down his operation. Filmed using an animation technique called interpolated rotoscope, with animation over filmed sequences.